A systematic review of Motivational Interviewing interventions in cancer patients and survivors. Issue 7 (July 2016) - Spencer, Jennifer C.; Wheeler, Stephanie B.
Highlights: We examine 15 studies using Motivational Interviewing in cancer patients/survivors. Lifestyle behaviors (diet, exercise, smoking) are most frequently addressed. Telephone-based MI and nurse counselors are common adaptations for this population. MI is a promising tool for eliciting behavior change in cancer patients/survivors. Abstract: Objective: To explore the use of Motivational Interviewing (MI) interventions among cancer patients and survivors, and determine aspects of intervention design that are common across successful MI interventions for this population. Methods: We conducted a systematic review of studies addressing behavior change in cancer patients or survivors using Motivational Interviewing techniques. Studies were categorized into three groups based on behavioral outcome; lifestyle behaviors, psychosocial outcomes, and cancer-related symptom management. Results: We included 15 studies in our analysis. Studies addressed behaviors such as diet, exercise, smoking cessation, cancer-related stress, and fatigue management. Counseling sessions varied in frequency and method of delivery, although telephone-based interventions were common. Trained oncology nurses often delivered MI sessions, and the majority of interventions included quality assessment to verify fidelity of MI techniques. Conclusion: Solid evidence exists for the efficacy of MI to address lifestyle behaviors as well as the psychosocial needs of cancer patients and survivors. More research is needed on the use of MI for self-management of cancer-related symptoms. Practice implications: Motivational Interviewing is a promising technique for addressing many types of behavior change in cancer patients or survivors. Intervention design must be sensitive to cancer type, phase of care, and complexity of desired behavior.